Information Security and Privacy 17th Australasian Conference, ACISP 2012, Wollongong, NSW, Australia, July 9-11, 2012. Proceedings - Susilo, Willy; Mu, Yi.; Seberry, Jennifer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 17th Australasian Conference on Information Security and Privacy, ACISP 2012, held in Wollongong, Australia, in July 2012. The 30 revised full papers presented together with 5 short papers were carefully reviewed and selected from 89 submissions. The papers are organized in topical sections on fundamentals; cryptanalysis; message authentication codes and hash functions; public key cryptography; digital signatures; identity-based and attribute-based cryptography; lattice-based cryptography; lightweight cryptography.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Coding theory; Information systems; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Coding and Information Theory; Computer Appl. in Administrative Data Processing; e-Commerce/e-business.